Grand Design Instrument of Potential Abilities for Placement Test (Program Studi Pendidikan Agama Islam, 2020)
This research aims to develop potential ability instruments for placement tests in graduate degrees. This study used the research and development instrument made by Hambleton and Jones sequences. The potential abilities measured by the instrument are academic potential and language skills. The product was reviewed by professional assessor and used in admission for selection in the academic years 2016/2017. The professional assessor reviewed the content, test construction, and language aspect. The construct and content validity from the professional assessor reached a good level with minor revision for the next selection. Ultimately, the results of the reviewing process are the potential academic test must not measure prior knowledge but the initial potential of the candidate and test for language should be emphasized on prior knowledge for Islamic study.